PERLINDUNGAN HUKUM PREVENTIF KEPADA KONSULTAN HUKUM PASAR MODAL DI INDONESIA (Studi Perbandingan Hukum Indonesia dan Singapura) - Halawa, Filemon; Situmeang, Ampuan; Amboro, FL Yudhi Priyo (Fakultas Syariah INSURI Ponorogo, 2023)
Indonesia as a sovereign country guarantees and provides protection for every citizen. This is a reflection of the State of Indonesia as a state of law. It is the same as the supporting profession of legal consultants in the capital market who have the right to have all their rights protected while carrying out their profession. The supporting profession of legal consultants in the capital market has an important role. Provisions of Article 67 of Law no. 8 of 1995 concerning the Capital Market which reads